The Military Injury Severity Score (mISS): A better predictor of combat mortality than Injury Severity Score (ISS). Issue 1 (July 2016) - Le, Tuan D.; Orman, Jean A.; Stockinger, Zsolt T.; Spott, Mary Ann; West, Susan A.; Mann-Salinas, Elizabeth A.; Chung, Kevin K.; Gross, Kirby R.
Abstract : BACKGROUND: The Military Injury Severity Score (mISS) was developed to better predict mortality in complex combat injuries but has yet to be validated. METHODS: US combat trauma data from Afghanistan and Iraq from January 1, 2003, to December 31, 2014, from the US Department of Defense Trauma Registry (DoDTR) were analyzed. Military ISS, a variation of the ISS, was calculated and compared with standard ISS scores. Receiver operating characteristic curve, area under the curve, and Hosmer-Lemeshow statistics were used to discriminate and calibrate between mISS and ISS. Wilcoxon-Mann-Whitney, t test and χ 2 tests were used, and sensitivity and specificity calculated. Logistic regression was used to calculate the likelihood of mortality associated with levels of mISS and ISS overall. RESULTS: Thirty thousand three hundred sixty-four patients were analyzed. Most were male (96.8%). Median age was 24 years (interquartile range [IQR], 21–29 years). Battle injuries comprised 65.3%. Penetrating (39.5%) and blunt (54.2%) injury types and explosion (51%) and gunshot wound (15%) mechanisms predominated. Overall mortality was 6.0%. Median mISS and ISS were similar in survivors (5 [IQR, 2–10] vs. 5 [IQR, 2–10]) but different in nonsurvivors, 30 (IQR, 16–75) versus 24 (IQR, 9–23), respectively ( p < 0.0001). Military ISS and ISS were discordant in 17.6% (n = 5, 352), accounting for 56.2% (n = 1, 016) of deaths. Among cases with discordant severity scores, the median difference between mISS and ISS was 9 (IQR, 7–16); range, 1 to 59. Military ISS and ISS shared 78% variability ( R 2 = 0.78). Area under the curve was higher in mISS than in ISS overall (0.82 vs. 0.79), for battle injury (0.79 vs. 0.76), non–battle injury (0.87 vs. 0.86), penetrating (0.81 vs. 0.77), blunt (0.77 vs. 0.75), explosion (0.81 vs. 0.78), and gunshot (0.79 vs. 0.73), all p < 0.0001. Higher mISS and ISS were associated with higher mortality. Compared with ISS, mISS had higher sensitivity (81.2 vs. 63.9) and slightly lower specificity (80.2 vs. 85.7). CONCLUSION: Military ISS predicts combat mortality better than does ISS. LEVEL OF EVIDENCE: Prognostic and epidemiologic study, level III. Abstract : Supplemental digital content is available in the text.